2014
DOI: 10.14214/sf.1159
|View full text |Cite
|
Sign up to set email alerts
|

Sequencing of harvester work during standard cuttings and in areas with windbreaks

Abstract: (2014). Sequencing of harvester work during standard cuttings and in areas with windbreaks. Silva Fennica vol. 48 no. 4 article id 1159. 16 p. Highlights• In standard cutting stands and thinning areas with windbreaks there occurred three-activity operational cycles. In mature stands with windbreaks the occurrence of stable sequences supplemented with five-activity cycles was noted. Consequently, the operational time in post-disaster thinning stands should be increased by 55% whereas in mature stands it should … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 13 publications
0
19
0
1
Order By: Relevance
“…In the study by Szewczyk et al [35], in the mature post-disaster stands, the share of moving time averaged 19% of the total effective time, and it was higher by almost 100% than in normal stands of undamaged standing trees. The share of moving time was, on average, 18% of the total effective time consumption in the clear-cutting stands of windfalls in this study.…”
Section: Evaluation Of the Main Findingsmentioning
confidence: 90%
See 1 more Smart Citation
“…In the study by Szewczyk et al [35], in the mature post-disaster stands, the share of moving time averaged 19% of the total effective time, and it was higher by almost 100% than in normal stands of undamaged standing trees. The share of moving time was, on average, 18% of the total effective time consumption in the clear-cutting stands of windfalls in this study.…”
Section: Evaluation Of the Main Findingsmentioning
confidence: 90%
“…For instance, Szewczyk et al [35] reported that the duration of a harvester operation cycle in stands with windbreaks is 28% longer in mature stands in comparison with normal forest stands. Kim et al [79] studied the effect of downed trees on harvesting productivity in beetle-killed stands.…”
Section: Evaluation Of the Main Findingsmentioning
confidence: 99%
“…For such data, a cyclicality of its occurrence can be determined, which was used in the study presented here. Having obtained a time series with the use of a moving average (equal weights), the single-band Fourier analysis was employed to detect a variable cyclical structure of the time series under investigation (Szewczyk et al 2014). With regard to the snap-back timing PSION calculation method, the duration of a work cycle was determined for regular, five-activity cycles.…”
Section: Discussionmentioning
confidence: 99%
“…Simultaneously, the DOD LS 430W video camera (DODTech, ON, Canada) mounted in the operator's cabin recorded the same work cycles. The duration of different activities in the work cycle was recorded to the nearest second (PSION method) or 0.1 s. (VIDEO method) and then classified according to the International Union of Forest Research Organisations (IUFRO) standards regarding forest work study nomenclature (Björheden 1991;IUFRO 1995;Szewczyk et al 2014) (Table 2). …”
Section: Site Detailsmentioning
confidence: 99%
See 1 more Smart Citation